Left Atrial Remodeling after Mitral Valve Repair for Primary Mitral Regurgitation: Evolution over Time and Prognostic Significance - Stassen Jan; van Wijngaarden Aniek L; Wu Hoi W; Palmen Meindert; Tomsic Anton; Delgado Victoria; Bax Jeroen J; Marsan Nina Ajmone (MDPI, 2022)
Left atrial (LA) dilatation is associated with worse outcomes in primary mitral regurgitation (MR). However, the effects of mitral valve repair on LA size and its prognostic implications are not well known. In the current study, LA volume index (LAVi) and LA reservoir strain (LASr) were evaluated immediately before and after surgery, and during long-term follow-up in 226 patients undergoing mitral valve repair for primary MR (age 62 +/- 13 years, 66% male). Mean LAVi was reduced significantly after surgery and at long-term follow-up (from 56 +/- 28 to 38 +/- 21 to 32 +/- 17 mL/m(2); p < 0.001). LASr reduced significantly after surgery but increased again during the long-term (from 23.6 +/- 9.4 to 11.5 +/- 5.0 to 17.3 +/- 7.5%; p < 0.001). Age, pre-operative LAVi, MR severity, and postoperative transmitral pressure gradient were associated with LA reverse remodeling by the long-term check-up. During a median follow-up of 72 (40-114) months, 43 (19%) patients died. Patients with LAVi >= 42 mL/m(2) at long-term follow-up showed significant higher mortality rates compared to patients with LAVI < 42 mL/m(2) (p < 0.001), even after adjusting for clinical covariates. In conclusion, significant LA reverse remodeling was observed both immediately and at long-term follow-up after mitral valve repair. LA dilatation at long term follow-up after surgery was still associated with all-cause mortality.